Stainless steel material

By controlling the concentrations of Al, Ca, and Mg, and incorporating CaO-MgO inclusions, the formation of slag spots is suppressed, stabilizing the cathode spot and enhancing weld penetration in stainless steel materials.

JP2025000288APending Publication Date: 2025-01-07NIPPON STEEL STAINLESS STEEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023100064
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing stainless steel materials suffer from slag spots (black spots) during welding due to the formation of oxide aggregates, which are not effectively addressed by previous proposals that control CaO/(SiO2 + MnO + CaO) ratios, leading to insufficient penetration and bead shape, and are prone to sunspots from TiN and TiO2 formation under practical welding conditions.

Method used

Control the concentrations of easily oxidizable elements like Al, Ca, and Mg within specific ranges, and include CaO-MgO inclusions to stabilize the cathode spot, ensuring the CaO/(MgO + Al2O3) ratio and (MgO + Al2O3 + CaO + Ti2O3) ratio are within certain limits, thereby suppressing slag spots and improving weld penetration.

Benefits of technology

Stabilizes the cathode spot during welding, prevents slag spots, and achieves deep penetration with good bead shape by controlling oxide inclusions, resulting in improved weld quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000288000001
    Figure 2025000288000001
  • Figure 2025000288000002
    Figure 2025000288000002
Patent Text Reader

Abstract

To provide a stainless steel material which has good penetration property, can suppress occurrence of slag spots and has an inclusion form suitable for weldability.SOLUTION: A stainless steel material has a predetermined component composition and satisfies the following Expression A and Expression B, wherein an average composition of an oxide-based inclusion of a surface layer satisfies Expression C and Expression D, thereby stabilizes a cathode point, and adopts a method for controlling amounts of MgO, Al2O3, CaO and Ti2O3 of the whole stainless steel material in such a way that the amounts are constant amounts or less, and thereby prevents a slag spot and has good penetration property. Expression A: Ca / (Mg+Al / 5)≥0.3, Expression B: Ti / 10+Al / 5+Ca+Mg / 2≤0.003, Expression C: 0.20≤CaO / (CaO+MgO+Al2O3)≤0.80, and Expression D: (MgO+Al2O3+CaO+Ti2O3) / (MgO+Al2O3+SiO2+CaO+Ti2O3+Cr2O3+MnO)≤0.50.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to stainless steel materials. [Background technology]

[0002] When arc welding is performed using stainless steel as the base material, defects called "slag spots (black spots)" in which oxide aggregates are scattered on the weld bead may occur. According to the description in Non-Patent Document 1, slag spots are minute slag that remain floating on the weld bead in island or dot form at intervals of several mm to several cm. It is thought that oxygen that enters the molten pool during arc welding reacts with active elements such as Al, Ca, and Ti, which are trace components in the steel, and remains as slag spots.

[0003] There have been several proposals to suppress slag spots. For example, Patent Document 1 discloses that the average CaO / (SiO 2 It has been proposed that the CaO-Al+MnO+CaO mass ratio should be controlled to 0.40 or less and the average CaO / MnO mass ratio should be controlled to 15.0 or less to make it difficult for slag spots to occur during welding. However, the concentrations of Al and Mg, which can form oxides during welding just like Ca, are also excessively reduced, and the CaO-Al concentration, which contributes to the stabilization of cathode spots during welding, is reduced. 2 O 3 -Since no MgO-based inclusions are produced during welding, the penetration depth during welding is small, and a sufficient bead shape may not be obtained. Also, depending on the amount of active elements other than Ca, such as Al and Ti, slag spots may occur.

[0004] For example, Patent Document 2 proposes a stainless steel material that suppresses the generation of black spots (slag spots) during welding by controlling the structure of nonmetallic inclusions. However, this steel material does not take into consideration the Ti that is mixed in small amounts in practical materials, and therefore, when a small amount of air is mixed into the shielding gas during welding in a practical environment, TiN, TiO 2Furthermore, because it contains excessive amounts of easily oxidizable elements such as Al and Ca, it was not taken into consideration that in practical environments, when a small amount of air is mixed into the shielding gas during welding, this can lead to the generation of black spots. In addition, under some welding conditions, the solid phase oxide MgO·Al 2 O 3 The formation of CaO-Al contributes to the stabilization of cathode spots in welding. 2 O 3 - In some cases, MgO-based inclusions were not formed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-77925 A [Patent Document 2] JP 2004-149833 A [Non-patent literature]

[0006] [Non-Patent Document 1] "Stainless Steel Handbook, 3rd Edition," edited by the Japan Stainless Steel Association, Nikkan Kogyo Shimbun, 1995, pp.1030-1031 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has an object to provide a stainless steel material which suppresses the occurrence of slag spots (black spots) during welding and improves weld penetration. [Means for solving the problem]

[0008] The inventors have developed an Al alloy suitable for cathode spot stabilization. 2 O 3 - The idea was that by including a certain amount of CaO-MgO inclusions, the penetration would be improved, while by controlling the amount of easily oxidizable elements within an appropriate range, the occurrence of slag spots (black spots) during welding would be suppressed. As a result of detailed research, the following findings were obtained.

[0009] (A) Aluminum on the surface of stainless steel 2 O 3 It was found that by appropriately controlling the concentrations of CaO and MgO, it is possible to stabilize the cathode spots and prevent them from dissolving in the steel during welding.

[0010] (i) Furthermore, it was discovered that by controlling the amounts of Ti, Al, Ca, and Mg, which are easily oxidizable elements in stainless steel, within specified ranges, it is possible to suppress slag spots even if the oxygen concentration increases during welding. The present invention has been made based on the above findings, and the gist of the present invention is as follows.

[0011] [1] The components are in mass%: C: 0.001% or more and 0.200% or less, Si: 0.10% or more and 3.00% or less, Mn: 0.10% or more and 15.00% or less, P: 0.040% or less, S: 0.0100% or less, Ni: 2.0% or more and 20.0% or less, Cr: 10.0% or more and 30.0% or less, Mo: 5.00% or less Cu: 5.00% or less, Ti: 0.001% or more and 0.010% or less, Al: 0.0001% or more and 0.0100% or less, O: 0.0010% or more and 0.0200% or less, N: 0.500% or less, Ca: 0.0001% or more and 0.0030% or less, Mg: 0.0001% or more and 0.0030% or less, B: 0.0100% or less, Nb: 0.60% or less, W: 5.00% or less, Sn: 0.50% or less, V: 0.50% or less, Co: Contains 1.00% or less, The balance is Fe and unavoidable impurities, Satisfying the following formula A and formula B Ca / (Mg+Al / 5)≧0.30 ...Formula A Ti / 10+Al / 5+Ca+Mg / 2≦0.0030 ...Formula B In the cross section of the steel material L, the average composition of oxide-based inclusions with a diameter of 1 μm or more that exist in a region from the surface to a depth of t / 8 in the depth direction, where t is the steel material thickness, satisfies the following formulas C and D. 0.20≦CaO / (CaO+MgO+Al 2 O 3 )≦0.80 ...Formula C (MgO+Al 2 O 3 +CaO+Ti 2 O 3 ) / (MgO+Al 2 O 3 +SiO 2 +CaO+Ti 2 O 3 +Cr 2 O 3 +MnO)≦0.50 ...Formula D 1. A stainless steel material comprising: However, each element in formula A and formula B indicates the mass% of the element in the stainless steel material, and if the element is not included, 0 is substituted. Also, each oxide in formula C and formula D is CaO, SiO 2 , Al 2 O 3 , MgO, Ti 2 O 3 , Cr 2 O 3 The mass percentage of each oxide is indicated when the total of MnO is 100 mass%, and if no oxide is included, 0 is substituted.

[0012] Here, the content of each of the above elements is the total content of the element present in the steel. Therefore, the content of metal elements and oxygen that are partly present as oxides includes the amount present as oxide. Effect of the Invention

[0013] According to the present invention, in addition to stabilizing the cathode spot during welding, it is possible to suppress slag spots and obtain a stainless steel material with good penetration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following description will be based on one embodiment of the present invention. The present invention is not limited to the embodiment introduced here. In this specification, one embodiment of the present invention may be simply referred to as the "present invention". In addition, the "%" indication of the content of each element and inclusion means "mass %" unless otherwise specified. In particular, when the content of each element does not specify a lower limit or the lower limit is 0%, it also includes the case where the element is not contained (0%). Furthermore, when an element symbol or a chemical formula of a compound is used in a formula, the content (mass %) of the element or compound is indicated, and when the element is not contained, 0 (%) is substituted. In addition, the form of the steel material is not particularly limited, and includes steel plate, steel bar, wire rod, steel shape, steel pipe, etc.

[0015] [Oxide inclusions in steel] First, the oxide inclusions in steel will be described. The inventors, through trial and error experiments, have found that arc weldability is stabilized and penetration is improved by controlling the content of oxide-based inclusions in steel, particularly the content of oxide-based inclusions with a grain size of 1 μm or more in the surface layer of the steel (hereinafter, unless otherwise specified, "inclusions" refers to oxide-based inclusions with a grain size of 1 μm or more in the surface layer of the steel), which stabilizes the cathode spot during welding and improves penetration. 2 O 3 It is preferable that the steel contains a certain amount of CaO-MgO inclusions. Here, the surface layer of the steel material refers to a region extending from the surface of the steel material to a depth of t / 8 in the depth direction, where t is the thickness of the steel material.

[0016] If there is an excess of CaO, it can cause slag spots, so it is advisable to keep the CaO content to a certain level. On the other hand, if the CaO content is too low, it can cause Al, which can become cathode spots. 2 O3 - The amount of CaO-MgO inclusions is reduced, and the stability of arc welding is impaired. 2 O 3 It is advisable to satisfy the relational expression (Equation C) of the ratio of CaO to the total of Al, CaO, and MgO (hereinafter referred to as the CaO ratio). By satisfying Equation C, the slag present on the molten pool when welding steel is in a molten state and does not insulate the arc discharge but acts as an appropriate cathode point, resulting in a steel material with a deep penetration and good bead shape. 2 O 3 The lower limit of the ratio of CaO to the total of CaO and MgO (CaO ratio) may be 0.20, and preferably 0.25, 0.30, 0.35, or 0.40. The upper limit of the CaO ratio may be 0.80, and preferably 0.75, 0.70, 0.65, or 0.60.

[0017] 0.20≦CaO / (CaO+MgO+Al 2 O 3 )≦0.80 ...Formula C

[0018] Next, in order to suppress the occurrence of slag spots (black spots) in steel, it is advisable to suppress the generation of oxides containing easily oxidizable elements in the oxide-based inclusions. Therefore, the ratio of oxide-based inclusions of easily oxidizable elements (MgO, Al) that cause slag spots to the total amount of oxide-based inclusions is calculated. 2 O 3 , CaO, Ti 2 O 3 In other words, by satisfying the following formula D, which shows the ratio of easily oxidizable inclusions, even if oxygen is mixed into the molten pool during welding, the amount of MgO, Al 2 O 3 , CaO, Ti 2 O 3 The small amount of easily oxidizable inclusions produced can suppress the occurrence of slag spots, and a steel product with good surface quality after welding can be obtained. The smaller the easily oxidizable inclusion ratio, the more preferable it is, and the upper limit of the ratio should be 0.50 or less, and preferably 0.45, 0.40, 0.35, 0.30, 0.25, or 0.20.

[0019] (MgO+Al 2 O 3 +CaO+Ti 2 O 3 ) / (MgO+Al 2 O 3 +SiO 2 +CaO+Ti 2 O 3 +Cr 2 O 3 +MnO)≦0.50 ...Formula D

[0020] When the oxide-based inclusions in steel satisfy the above formula C (CaO ratio) and formula D (easily oxidizable inclusion ratio), stable arc welding can be performed and the occurrence of slag spots can be suppressed. However, the oxides in formulas C and D are CaO, SiO 2 , Al 2 O 3 , MgO, Ti 2 O 3 , Cr 2 O 3 The mass% of each oxide is shown when the total of Mg, Al, Si, Ca, Ti, Cr, and MnO is taken as 100 mass%, and 0 is substituted if the oxide is not included. The content of each oxide is calculated by dividing the content of Mg, Al, Si, Ca, Ti, Cr, and Mn contained in the inclusion by the content of each oxide, MgO, Al 2 O 3 , SiO 2 , CaO, Ti 2 O 3 , Cr 2 O 3 The content of each of the converted oxides is calculated based on the total content of the converted oxides.

[0021] [Method of measuring oxide composition] Using SEM, EDX, etc., for the longitudinal cross section (L cross section) of the steel material, an arbitrary 5 mm 2The number, area and chemical composition of inclusions with a grain size (equivalent diameter of a circle with an equal area) of 1 μm or more in the observation area are measured and converted into the inclusion number density. The content of each oxide is calculated by dividing the content of Mg, Al, Si, Ca, Ti, Cr and Mn contained in the oxide-based inclusion by the content of each oxide, MgO, Al 2 O 3 , SiO 2 , CaO, Ti 2 O 3 , Cr 2 O 3 The average composition of the inclusions observed is calculated based on the EDX analysis results. At this time, the average composition of the inclusions is calculated by multiplying the area of ​​each inclusion by the calculated CaO, SiO 2 , Al 2 O 3 , MgO, Ti 2 O 3 , Cr 2 O 3 The total concentration of MnO is taken as 100 mass%, and the mass percentage of each oxide is expressed relative to that.

[0022] [component] Next, the components of the stainless steel material according to the present invention will be described.

[0023] Since C is an austenite stabilizing element and also an element that improves strength, it is preferable that the content be 0.001% or more, and preferably 0.004% or more. On the other hand, if C is present in excess, it generates Cr carbides, which reduces corrosion resistance and also significantly reduces workability, so it is preferable that the content be 0.200% or less, and preferably 0.100% or less.

[0024] Silicon is an element that contributes to deoxidation, and the more it is added, the lower the basicity of the inclusions and the softer they become. There is no need to add silicon, but it may be added as a pre-deoxidizer before adding aluminum. If silicon is added, it should be 0.10% or more to achieve its effect, and preferably 0.40% or more. However, excessive addition of silicon leads to a decrease in workability, so it should be 3.00% or less, and preferably 1.00% or less.

[0025] Mn is an austenite stabilizing element and also contributes to deoxidation like Si, and the more it is added, the lower the basicity of the inclusions and the softer they become. To achieve this effect, Mn should be added at 0.10% or more, and preferably at 0.30% or more. However, excessive addition of Mn leads to a decrease in workability and corrosion resistance, so the content should be 15.00% or less, and preferably 10.00% or less, or 5.00% or less.

[0026] P is an element contained as an impurity in the main raw materials such as molten iron and ferrochrome. Since P is an element that is the main cause of the decrease in hot ductility, it is better to reduce the P content as much as possible. From this viewpoint, the P content is preferably 0.040% or less, and more preferably 0.030% or less. However, since an excessive reduction in the content leads to an extreme increase in costs, a content of 0.005% or more may be acceptable for practical operation.

[0027] S is harmful to stainless steels, as it reduces toughness, hot workability, and corrosion resistance, so the less the better, and it is best to keep it below 0.0100%. However, excessive reductions would result in high loads during refining or the need to use expensive raw materials, so in practical operations, it is acceptable to contain 0.0001% or more.

[0028] The addition of Ni has the effect of further enhancing the high corrosion resistance of stainless steel. When Ni is added, it is recommended that the content be 2.0% or more to obtain this effect, and preferably 6.0% or more. However, since Ni is an expensive element, adding more than 20.0% does not provide an effect that is commensurate with the increase in alloy cost, so it is recommended that the content be 20.0% or less, and preferably 16.0% or less.

[0029] Cr is an element that gives stainless steel corrosion resistance, and should be contained at 10.0% or more, preferably 15.0% or more. On the other hand, a large content of Cr leads to a decrease in workability, so it should be 30.0% or less, preferably 22.0% or less.

[0030] Mo has the effect of improving corrosion resistance. It is not necessary to add Mo, and the lower limit is 0%, but if Mo is added, it is better to add 0.01% or more to obtain this effect, and preferably 0.02% or more. On the other hand, if the Mo content is too high, the workability decreases, so it is better to keep it at 5.00% or less, and preferably 3.00% or less.

[0031] The addition of Cu has the effect of further enhancing the high corrosion resistance of stainless steel and improving its workability. Cu does not have to be contained, with the lower limit being 0%, but if it is contained, it is better to contain 0.01% or more to obtain this effect, and preferably 0.05% or more. On the other hand, excessive addition does not improve performance to justify the manufacturing cost, so it is better to keep it at 5.00% or less, and preferably 1.50% or less.

[0032] When Ti is oxidized during welding, it forms CaO-TiOx oxides with Ca, which contributes to stabilizing cathode spots. Therefore, the Ti content should be 0.001% or more. On the other hand, if Ti is contained in excess, coarse TiN and TiOx precipitate due to air contamination during welding, which can cause slag spots and stringers. To solve this problem, the Ti content should be 0.010% or less, and preferably 0.005% or less.

[0033] Al is Al 2 O 3 --CaO-MgO inclusions are formed, and contribute to the stabilization of cathode spots. Therefore, it is advisable to add 0.0001% or more, and preferably 0.0005% or more, or 0.0010% or more. On the other hand, if it is added in a large amount, it may cause the formation of spinel (MgO·Al 2 O 3 ) formation and deteriorates the product quality, so it is best to keep it at 0.0100% or less, and preferably at 0.0050% or less.

[0034] O is SiO 2It is an element that promotes the softening of inclusions by its formation, and should be 0.0010% or more, preferably 0.0020% or more. If it exists in excess of 0.0200%, coarse Cr 2 O 3 This reduces the corrosion resistance, so the content should be 0.0200% or less, and preferably 0.01% or less.

[0035] Since excessive N content leads to deterioration of workability, the content should be 0.500% or less, preferably 0.300% or less. There is no particular lower limit for the N content, but since excessive reduction increases the load during refining, in practical operation, the N content may be 0.001% or more.

[0036] Ca is Al 2 O 3 --CaO-MgO inclusions are formed, and Ca is contained in an amount of 0.0001% or more, preferably 0.0003% or more, 0.0005% or more, or 0.0010% or more, because Ca contributes to stabilizing cathode spots. On the other hand, if Ca is contained in a large amount, it increases the number of large inclusions in the molten steel stage. Therefore, the Ca content should be 0.0030% or less, and more preferably 0.0020% or less.

[0037] Mg is Al 2 O 3 --CaO-MgO inclusions are formed, and contribute to the stabilization of cathode spots. Therefore, it is advisable to include 0.0001% or more, and preferably 0.0003% or more, 0.0005% or more, or 0.0007% or more. On the other hand, if it is included in a large amount, it may cause the formation of spinel (MgO·Al 2 O 3 ) formation and deteriorates product quality. Therefore, it is advisable to keep it at 0.0030% or less, and preferably at 0.0020% or less.

[0038] B is an element that increases the strength of grain boundaries and contributes to improving workability. It is not necessary to contain B, with the lower limit being 0%, but if it is contained, in order to express this effect, it is preferable to contain 0.0001% or more, and preferably 0.0005% or more. On the other hand, excessive addition of B leads to a decrease in elongation and therefore a decrease in workability, so the content should be 0.0100% or less, and preferably 0.0050% or less.

[0039] Nb has the effect of improving formability and corrosion resistance. It is not necessary to add Nb, and the lower limit is 0%, but if it is added, it is better to add 0.10% or more to obtain this effect. On the other hand, if it is too much, recrystallization becomes difficult and the structure becomes coarse, so it is better to keep it at 0.60% or less, and preferably at 0.50% or less.

[0040] W, like Mo, has the effect of improving corrosion resistance. It is not necessary to contain W, with the lower limit being 0%, but if W is contained, in order to obtain this effect, it is preferable to contain 0.01% or more, and preferably 0.02% or more. On the other hand, if the W content is too high, the strength increases excessively and the workability decreases, so it is preferable to keep it at 5.00% or less, and preferably 3.00% or less.

[0041] Adding Sn has the effect of further enhancing the high corrosion resistance of stainless steel. It is not necessary to add Sn, with the lower limit being 0%, but if added, in order to obtain this effect, it is advisable to add 0.01% or more, and preferably 0.02% or more. On the other hand, excessive addition leads to a decrease in workability, so it is advisable to add 0.50% or less, and preferably 0.30% or less.

[0042] V is an element that forms VN and suppresses the deterioration of corrosion resistance caused by the precipitation of Cr nitrides. This effect is obtained when the V content is 0.01% or more. However, excessive addition leads to a deterioration of workability, so if V is contained, it is best to keep it at 0.50% or less.

[0043] Co, like Mo, has the effect of improving corrosion resistance. It is not necessary to contain Co, with the lower limit being 0%, but if it is contained, it is better to contain 0.01% or more to obtain this effect, and preferably 0.02% or more. On the other hand, strict control of Co is required due to its toxicity, so if Co is contained, it is better to keep it at 1.00% or less, and preferably 0.10% or less.

[0044] [Ca / (Mg+Al / 5)≧0.30] In order to ensure that the inclusions in the steel have the aforementioned CaO ratio (formula C) and easily oxidizable inclusion ratio (formula D) within the specified range, a study was conducted from the viewpoint of component composition. As a result, it was discovered that the CaO ratio can be kept within the specified range by setting the Ca content relative to the Al and Mg contents in an appropriate range. When the ratio of Ca to (Mg+Al / 5) is small, the CaO ratio (formula C) becomes small, and the inclusions present near the steel surface become CaO / (MgO+Al 2 O 3 As a result, the alloy becomes a high melting point oxide with a low CaO (+CaO) ratio, which insulates the arc discharge and therefore cannot stabilize the cathode spot, resulting in poor penetration. Therefore, the CaO ratio (formula C), which is the ratio of the Ca content to the Al and Mg contents, is set to 0.30 or more. It is preferably 0.35 or more, 0.40 or more, 0.45 or more, or 0.50 or more. There is no particular upper limit for the CaO ratio, but since too much CaO makes slag spots more likely to occur, it is preferably 2.00 or less.

[0045] Ca / (Mg+Al / 5)≧0.30 ...Formula A However, each element in the formula indicates the mass% of that element in the stainless steel material, and if the element is not included, 0 is substituted.

[0046] [Ti / 10+Al / 5+Ca+Mg / 2≦0.0030] By limiting the amounts of easily oxidizable elements Ti, Al, Ca, and Mg in steel, it is possible to suppress the generation of easily oxidizable oxides and to suppress the occurrence of slag spots even if the oxygen concentration rises during welding. It has been found that the contents of easily oxidizable elements Ti, Al, Ca, and Mg should satisfy the following formula B. Ti / 10+Al / 5+Ca+Mg / 2 should be 0.0030 or less, and preferably 0.0020 or less, or 0.0010 or less. If formula B is not satisfied, the easily oxidizable elements MgO, Al, and 2 O 3 , CaO, Ti 2 O 3 A large amount of oxides that cause slag spots are generated, making it easier for slag spots to form that are visible to the naked eye.

[0047] Ti / 10+Al / 5+Ca+Mg / 2≦0.0030 ...Formula B However, each element in the formula indicates the mass% of that element in the stainless steel material, and if the element is not included, 0 is substituted.

[0048] The balance of the above steel components is Fe and inevitable impurities. The inevitable impurities herein refer to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.

[0049] Next, the manufacturing method of the above stainless steel and stainless steel material will be described. In manufacturing the above stainless steel, the raw materials are melted and refined to produce stainless steel with adjusted composition. AOD and / or VOD can be used in the refining process.

[0050] In this embodiment, in the refining process, after reduction refining with Si or Al, metallic raw materials (ferroalloy, ordinary steel, and / or stainless steel scrap, etc.) are added, and the contents of predetermined elements are controlled to satisfy formulas A and B, to obtain molten steel.

[0051] After the refining step, the steel plate may be manufactured according to a conventional method. For example, in the case of steel plate, the molten steel refined after melting is formed into a billet of a predetermined square size or a slab of a predetermined size by a continuous casting method or an ingot casting-blooming method.

[0052] The billets or slabs are then rolled to a desired thickness through a hot rolling process, after which the plates may be annealed and / or pickled and / or further cold rolled, depending on the required dimensions. EXAMPLES

[0053] The present embodiment and a comparative example will be described below.

[0054] 100 kg of stainless steel having each composition of Steel Nos. A1 to A6 and a1 to a3 shown in Table 1 was melted in a vacuum furnace. When the steel reached the specified temperature, it was tapped and produced as a steel ingot measuring 150 x 150 x 550 mm. Then, each steel ingot was hot rolled, annealed, pickled, and cold rolled to obtain a plate material with a thickness of 3 mm. Samples were taken from the obtained plate material for inclusion evaluation, surface quality evaluation, and welding evaluation.

[0055] The collected samples were then cut, and the cross sections (L cross sections) parallel to the rolling direction and plate thickness direction were polished with emery paper and buffed to a mirror finish. An SEM (scanning electron microscope) was then used to measure the surface area of ​​the steel material (the area from the surface to a depth of t / 8 on both sides of the plate thickness t (in this case, the area from the surface to a position 0.375 mm away)). 2 The number of inclusions present on the observation surface was counted, and the chemical composition of inclusions with a particle size of 1 μm or more was measured using EDS (energy dispersive X-ray analysis) to determine the level of contamination and the type of inclusion, and the number density and average composition of the inclusions were calculated.

[0056] The collected samples were subjected to bead-on-plate welding and weldability evaluation. A tungsten electrode (diameter 3 mm) was used, and argon gas was used as the shielding gas at 10 L (liters) / min. The welding was performed with an arc length of 3.0 mm, a welding current of 80 A, and a feed rate of 10 cm / min so as not to produce a back bead. The weld penetration depth h and bead width W were measured from the bead shape in the cross section perpendicular to the welding direction of the obtained welded test piece. Since the smaller the ratio W / h of bead width W to penetration depth h, the better the quality, a specimen with a W / h of 5 or less was judged to have sufficient weld penetration and was judged to pass (marked with a circle), and any other specimen was judged to fail (marked with an x).

[0057] The surface of the test piece after welding was visually observed, the number of slag spots was counted, and surface defects were evaluated. The average number of surface defects caused by nonmetallic inclusions on the entire surface of the sample was 0.1 pieces / cm 2 If the average number of surface defects is less than 0.1 / cm, it can be said that the occurrence of slag spots is suppressed. 2 The following were judged as pass (marked with a circle), and the rest were judged as fail (marked with an x). The results are shown in Table 2.

[0058] In the steels No. A1 to A6 in Table 1, the amounts of Ti, Al, Ca, and Mg were controlled, so that the composition of inclusions with a particle size of 1 μm or more in the surface layer satisfied the range of formula C, which contributed to the stabilization of the cathode spots, resulting in a small W / h during welding and good penetration during welding. Furthermore, the average composition of the inclusions, MgO+Al 2 O 3 +CaO+Ti 2 O 3 The range of formula D was satisfied, and there were few slag spots after welding.

[0059] Steel No. a1 in Table 1 did not satisfy the conditions of formula A, and since the CaO ratio in the inclusion composition was small, the inclusions contributing to cathode spot stabilization were insufficient, and the steel failed the weldability evaluation.

[0060] Steels No. a2 and a3 in Table 1 did not satisfy the condition of formula B, and had a high ratio of easily oxidizable inclusions in the inclusion composition, so that the number of slag spots generated after welding was large and they failed the surface defect evaluation.

[0061] [Table 1]

[0062] [Table 2] [Industrial Applicability]

[0063] INDUSTRIAL APPLICABILITY The present invention can be utilized in the stainless steel manufacturing industry, and the obtained stainless steel material can be widely utilized in many industrial fields such as the machinery industry and the construction industry.

Claims

[Claim 1] The components are expressed as follows, by mass%: C: 0.001% or more and 0.200% or less, Si: 0.10% or more and 3.00% or less, Mn: 0.10% or more and 15.00% or less, P: 0.040% or less, S: 0.0100% or less, Ni: 2.0% or more and 20.0% or less, Cr: 10.0% or more and 30.0% or less, Mo: 5.00% or less, Cu: 5.00% or less, Ti: 0.001% or more and 0.010% or less, Al: 0.0001% or more and 0.0100% or less, O: 0.0010% or more and 0.0200% or less, N: 0.500% or less, Ca: 0.0001% or more and 0.0030% or less, Mg: 0.0001% or more and 0.0030% or less, B: 0.0100% or less, Nb: 0.60% or less, W: 5.00% or less, Sn: 0.50% or less, V: 0.50% or less, Co: 1.00% or less; The balance is Fe and unavoidable impurities, Satisfying the following formula A and formula B, A stainless steel material characterized in that, in a cross section (L) of the steel material, the average composition of oxide-based inclusions having a particle size of 1 μm or more present in a region from the surface to a depth of t / 8 in the depth direction, where t is the steel material thickness, satisfies the following formulas C and D. Ca / (Mg+Al / 5)≧0.30 ...Formula A Ti / 10+Al / 5+Ca+Mg / 2≦0.0030 ...Formula B 0.20≦CaO / (CaO+MgO+Al 2 O 3 )≦0.80 ...Formula C (MgO+Al) 2 Oh 3 +CaO+Ti 2 Oh 3 ) / (MgO+Al) 2 Oh 3 +SiO 2 +CaO+Ti 2 Oh 3 +Cr 2 Oh 3 +MnO)≦0.50 ...Formula D However, each element in formula A and formula B indicates the mass% of the element in the stainless steel material, and if the element is not included, 0 is substituted. Also, each oxide in formula C and formula D is CaO, SiO 2 , Al 2 O 3 , MgO, Ti 2 O 3 , Cr 2 O 3 The mass percentage of each oxide is indicated when the total of MnO is taken as 100 mass %, and if no oxide is included, 0 is substituted.

Citation Information

Patent Citations

  • Stainless steel excellent in corrosion resistance, weldability, and surface properties and its production method

    JP2004149833A

  • Stainless steel material excellent in slag spot generation inhibition performance, weld structural part, and manufacturing method therefor

    JP2019077925A